Assessment of the Costs Associated with Outpatient and Inpatient Treatment of ARVI and Influenza and its Complications - Z. Sh. Nurmatov (Эпидемиология и вакцинопрофилактика, 2015)
In this paper the authors are presenting the analysis of an economic burden caused by influenza and acute respiratory viral infections (ARVI). This is the first study of its kind in the Kyrgyz Republic. The goal of the study was to calculate the economic burden caused by the flu and ARVI morbidity in the Republic. The study was done during 2013 - 2014 on the basis of two hospitals among inpatients and in the basis of a policlinic in the city of Bishkek among outpatients. We found that the cost of one case of flu or ARVI was 4771.41 kyrgyz som (USD 97.79). In the overall structure, the cost of medical expenses was lower than the cost of non-medical expenses (41.3 compared to 58.7%). Results of this study allowed for the first time in Kyrgyzstan to calculate the total cost for treatment of ARVI and influenza in the country. For the year 2013 they amounted to 636 516 889.2 kyrgyz som or USD 13,835,558.85. Results of the study allowed determining the factors that influence the costs that medical institutions and patients face, as well as come up with recommendations on the need for preventive vaccination against influenza.